Impulse Buying Behaviour in Live Streaming Shopping Using the Stimulus-Organism-Response Framework - Zhafirah, Sasqia; Mulyaningtyas, Dian (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
The aim of this study is to identified the influence between individual characteristics variables, situation stimulus, social media, digital marketing, which influence the implicit purchasing behavior variable (Y) in live streaming shopping with hedonistic motivation. (Z). Samples were taken from as many as 150 respondents, processing data using Smart PLS. The results of the t (significance) test show that individual characteristics, situation stimuli, and digital marketing have a positive and significant influence on implicit purchasing behaviour in live streaming purchases, social media have a negative and significant impact on implied buying behavior in steaming live purchases. Results of the analysis of variables show hedonistic motivation can affect individual characteristic, incentives in situations, Social media, digital marketing on the results of implicit buying behaviours in live stream purchases have a significant positive influence, and hedonist motivations can affect the perception of facility for implicit shopping behaviors in live streaming purchases with a positive, significant impact.